Pengaruh Customer Trust dan Fitur Live Streaming pada Aplikasi Shopee Terhadap Impulse Buying dalam Pembelian Produk Fashion dan Aksesoris Oleh Masyarakat: Studi pada Masyarakat Kota Surabaya - Erlinda Dwi Prastiwi; Ety Dwi Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the influence of customer trust and live streaming features on impulse buying in the purchase of fashion products and accessories by the residents of Surabaya city through the Shopee application. This research is quantitative in nature, involving a sample of 100 Shopee application users in Surabaya city. The sampling method employed is non-probability, specifically purposive sampling, with respondents aged between 17-40 years old, users of the Shopee application, who have made at least one purchase of fashion products and accessories through live streaming on the Shopee e-commerce platform, and residing in Surabaya city. Data collection is conducted online by distributing questionnaire links to the respondents. The results of this study indicate that both customer trust and live streaming have a significant simultaneous effect on impulse buying. Customer trust has a significant partial effect on impulse buying, while live streaming also has a significant partial effect on impulse buying.